Directly Attention loss adjusted prioritized experience replay - Zhuoying Chen; Huiping Li; Zhaoxu Wang (Complex & Intelligent Systems)
Abstract Prioritized Experience Replay enables the model to learn more about relatively important samples by artificially changing their accessed frequencies. However, this non-uniform sampling method shifts the state-action distribution that is originally used to estimate Q-value functions, which brings about the estimation deviation. In this article, a novel off-policy reinforcement learning training framework called Directly Attention Loss Adjusted Prioritized Experience Replay (DALAP) is proposed, which can directly quantify the changed extent of the shifted distribution through Parallel Self-Attention network, enabling precise error compensation. Furthermore, a Priority-Encouragement mechanism is designed to optimize the sample screening criteria, and enhance training efficiency. To verify the effectiveness of DALAP, a realistic environment of multi-USV, based on Unreal Engine, is constructed. Comparative experiments across multiple groups demonstrate that DALAP offers significant advantages, including faster convergence and smaller training variance.